Pembuktian Secara Hukum Terhadap Status Anak Yang Lahir Luar Perkawinan Dalam Perspektif Hukum Perdata. - Bernadus Bayo (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACTAccording to the sound of article 43 paragraph (1) is new in the Judicial Review of that which is a word that reads "children born outside of marriage have a relationship civil with her mother and her mother's family, as well as with the male as the father of bias evidenced by the science and technology and tools other evidence which by law have a relationship of blood, including blood relations with his father's family. This study aims to determine the legal consequences for a child born outside of marriage after the court ruling No. 46 / PUU / VIII / 2010 and to determine the relationship of civil child born out of wedlock with her biological father after the court ruling No. 46 / PUU-VIII / 2010 , This type of research legal normative legal research done by menenliti library materials or secondary data alone. The nature of research is descriptive analysis by describing or presenting and explaining a state that is based on the symptoms and facts obtained were then assessed based on the literature dealing with the problems examined. Penggumpulan data in this study using techniques of collecting legal material made through the study of literature that is gathering material law, both primary and secondary legal materials related to the study of literature, covering literature and documentary studies. The results of this study indicate that the Constitutional Court decision No. 46 / PUU / VIII / 2010 make children yanag born outside of mating as a party that has no legal status (persona in judicio) in the practice of inheritance in court and the right to receive inheritance biological father with provision being able to prove their berdasrkan blood relation of science and technology and or other evidence according to the law and the decision of the Court, the relationship between children born outside of mating with her father is a blood relation in the biological sense is confirmed by the legal process. Constitutional Court decision opens the possibility of legal discovery legal subjects that should be responsible for the child outside of mating to act as father through legal mechanisms by using evidence based science and technology and the leading edge or the law. Upon analysis, the logic of this decision legal consequences their child nasab extramarital relationship with her biological father, their rights and obligations between a child out of wedlock with her biological father, either in the form of income, inheritance and so forth.Keywords: Status of Children Born Outside of Marriage, Legal Proof of Civil Law.